Stable isotope composition of a vertebrate assemblage from the Tacuarembó Formation, Uruguay (Late Jurassic-Early Cretaceous): Geochemical insight into an arid continental environment - Leuzinger, Léa Sylvia (2019)
The Late Jurassic–Early Cretaceous Tacuarembó Formation (Uruguay) consists of aeolian dunes, ephemeral and perennial river deposits that are part of the vast Botucatu Desert, Parana Basin. It preserved a diverse vertebrate assemblage of great importance, considering the scarcity of continental fossil records of that period in Gondwana, and of vertebrate body fossils from paleodeserts worldwide. Isotopic studies on vertebrates of these settings and age are also rare; however they are important to precise paleoenvironmental and paleoclimatic parameters. We ran oxygen (δ18O) and carbon (δ13C) stable isotope analyses (n=21) on theropods, crocodyliforms and fish teeth of the Batoví Member at the UNIL, Switzerland. Clear and consistent differences between the δ18Ophosphate of enamel and dentine, and between the δ18Ophosphate and δ18Ostructural carbonate of the same fossils speak for a good preservation of the isotopic signature in enamel. The δ18Ophosphate of tooth enamel (22.6‰VSMOW), heavy for continental settings, 53 indicates an arid climate inducing strong evaporation of the local water, in agreement with the harsh conditions generally described for inner Gondwana at that period. Our results are comparable with other isotopic studies on contemporaneous sites from central Africa, also occupying an inland paleogeographical position. Estimates based on preexisting equations yield water temperatures of 20–25°C and a δ18Owater of ~0.4‰VSMOW. The δ13Cstructural carbonate of theropod enamel (–7.6‰VPDB), much lower than in crocodiles (–4.0‰VPDB) and bony fish (–1.6‰VPDB), suggests that the diet of theropods was principally composed of terrestrial animals, and not on aquatic nor semiaquatic preys.